2001
DOI: 10.1103/physrevlett.86.2641
|View full text |Cite
|
Sign up to set email alerts
|

Strong Linear-kValence-Band Mixing at Semiconductor Heterojunctions

Abstract: This paper examines linear-k terms in the G 8 valence-band Hamiltonian for heterostructures of zincblende-type semiconductors. In bulk crystals such terms are known to be extremely small, due to their origin as relativistic perturbations from d and f orbitals. However, in heterostructures there is a nonvanishing contribution from p orbitals. This contribution is an order of magnitude larger than the corresponding bulk term, and it should give rise to an optical anisotropy comparable to (although smaller than) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Recent reports suggest that additional spin-orbit effects at the surface may be responsible for the enhanced anisotropy. For the interfaces of heterostruc-tures it was shown that interface induced asymmetry may lead to spin-orbit splitting effects that are one order of magnitude higher than what is expected for the bulk system [151].…”
Section: Influence Of the In-plane Electric Field On The Anisotropymentioning
confidence: 99%
“…Recent reports suggest that additional spin-orbit effects at the surface may be responsible for the enhanced anisotropy. For the interfaces of heterostruc-tures it was shown that interface induced asymmetry may lead to spin-orbit splitting effects that are one order of magnitude higher than what is expected for the bulk system [151].…”
Section: Influence Of the In-plane Electric Field On The Anisotropymentioning
confidence: 99%
“…The latter representation has been used in the construction of the linear part of the Hamiltonian (2) [12]. In the semiconductor physics in the analysis of the transport properties in high electric fields it is common to assume that the charge carrier state is characterized by a particular energy in the energy band.…”
Section: Spin Surfaces In a 3 B 5 Compoundsmentioning
confidence: 99%
“…Linear-k mixing within Γ 8 valence states (heavy-and light-mass bands) was considered by Kane [8,9] and its contribution was evaluated by k · p and LMTO (linear muffin-tin orbitals) methods by Cardona et al [10,11]. The linear-k Hamiltonian for both Γ 8 and Γ 7 (split-off) valence bands in bulk semiconductors and heterostructures was recently evaluated by Foreman [12], who demonstrated that its contribution in heterostructures is by an order …”
Section: Linear-k Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the calculations, linear-k part of the Hamiltonian was taken from Ref. [15]. From the numerical calculations presented in [4,5] it follows that the inclusion of linear-k terms gives, in general, negligible effect on the shape of the spin surfaces in all A 3 B 5 semiconductors.…”
Section: General Casementioning
confidence: 99%